Effects of an acute enteric disease challenge on IGF-1 and IGFBP-3 gene expression in porcine skeletal muscle - Johnson, B.J.; Kayser, J.P.; Dunn, J.D.; Waylan, A.T.; Drtiz, S.S.; Nietfeld, Jerome C.; Minton, J. Ernest (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eighteen pigs (initial weight 25 lb and approximately 5 wk of age) were used in a 14-d trial to determine the effects of an acute Salmonella enterica serotype typhimurium (ST) disease challenge on both circulating insulinlike growth factor-1 (IGF-1) and insulin-like growth factor binding protein-3 (IGFBP-3) and steady-state IGF-1 and IGFBP-3 mRNA levels in skeletal muscle. Muscle biopsies and blood samples were obtained from all pigs on d 0, 3, 7, and 14 relative to ST-challenge. Results suggest that an acute ST-challenge decreased circulating IGF-1 levels on d 3 and 7 but did not affect circulating IGFBP-3 concentrations. Additionally, ST-challenge had no effect on steady-state IGF-1 and IGFBP-3 mRNA levels in skeletal muscle following the onset of disease. These data suggest that an acute enteric disease insult can lower circulating IGF-1 but more chronic conditions may be necessary to affect local IGF-1 levels in skeletal muscle. Additionally, the increased muscle IGF-1 mRNA without increased IGFBP-3 levels on d 14 most likely results in increased IGF-1 synthesis that contributes to circulating IGF-1 concentrations.
Keywords: Pigs; Salmonella; Muscle; IGF-1, IGFBP-3; Swine